Evening with Kevin Smith - Smith, Kevin, 1970-; Kenny, J. M.; New Wave Entertainment; Columbia TriStar Home Entertainment (Firm) (Culvor City, CA New Wave Entertainment, 2002)
An Evening With Kevin Smith is a no-holds-barred Q&A with one of Hollywood's most gifted filmmakers. Infamous for picking apart the pop culture landscape with films such as Clerks, Mall rats, Chasing Amy, Dogma, and Jay and Silent Bob Strike Back, the New Jersey native has become a veritable icon of in dependent film. Smith gives us a new lens to examine spirituality, sexuality, and human relationships. Get up close and - at times - very personal, with the man everyone has been waiting to hear from ... Silent Bob speaks!
Produced and directed by J.M. Kenny.
Rated: 18A (Ont.).
Closed-captioned.
115516
Keywords: Smith, Kevin, -- 1970 -- Interviews; Motion picture producers and directors -- United States -- Interviews; United States; Interviews